2021
DOI: 10.5005/jp-journals-10005-1811
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Conventional, Game-based, and Self-made Storybook-based Oral Health Education on Children\'s Oral Hygiene Status: A Prospective Cohort Study

Abstract: A bstract Introduction Dental caries is the most widespread disease affecting children worldwide. The reason for this increased prevalence is the use of more processed foods and beverages with the addition of refined sugars. General health affects oral health and its maintenance is of great importance. Lifestyle modifications and habits are formed at an early age therefore health education plays an important role in educating them about the prevention of problems related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…These findings were in accordance with previous studies by Kashyap et al [ 10 ], which showed that game-based education (i.e., crosswords and quiz with a PowerPoint presentation) proved very effective in improving oral health knowledge. Our findings are in accordance with those of Sharma et al [ 19 ], Malik et al [ 3 ], and Maheswari et al [ 20 ], who used game-based OHE to improve knowledge, health behaviour, and practices. The studies by Sinor et al [ 8 ] and Anwar et al [ 25 ] also reported that a cartoon-animated audiovisual aid significantly promoted knowledge regarding oral hygiene maintenance, in comparison to those who attended the conventional oral health talk.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings were in accordance with previous studies by Kashyap et al [ 10 ], which showed that game-based education (i.e., crosswords and quiz with a PowerPoint presentation) proved very effective in improving oral health knowledge. Our findings are in accordance with those of Sharma et al [ 19 ], Malik et al [ 3 ], and Maheswari et al [ 20 ], who used game-based OHE to improve knowledge, health behaviour, and practices. The studies by Sinor et al [ 8 ] and Anwar et al [ 25 ] also reported that a cartoon-animated audiovisual aid significantly promoted knowledge regarding oral hygiene maintenance, in comparison to those who attended the conventional oral health talk.…”
Section: Discussionsupporting
confidence: 93%
“…Studies have demonstrated that cartoon-animated audiovisual aids and game-based education implemented for schoolchildren are powerful tools for educating and providing thought-stimulating methods of learning [ 16 , 17 ]. The use of fun-based learning interventions (connect the dots games [ 1 , 18 ], crosswords and quizzes [ 3 ], flashcards [ 1 ], snakes and ladders [ 19 , 20 ], augmented reality board games [ 21 ], video games [ 22 , 23 ], smartphone oral hygiene applications [ 24 ], and animated audiovisual resources [ 25 ]) have been suggested to be a perfect motivating tool to encourage children to take part in self-care activities. The use of gaming in OHE can be a good alternative for educating basic health concepts, thereby, strengthening cognitive development and confidence [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…study, 24 which examined the effect of individual training on elementary school children's tooth‐brushing skills and discovered that children who received individual training improved significantly more than those in the control group who received group‐based training. Several previous studies confirmed the larger effectiveness of other interactive oral hygiene targeting interventions in comparison to the conventional approaches 25,26–29 . Most of those interventional strategies were game based, such as using flashcards, connecting the dots, 28 completing crosswords and quizzes, 27 snake and ladder, self‐made story books 29 …”
Section: Discussionmentioning
confidence: 69%
“…Several previous studies confirmed the larger effectiveness of other interactive oral hygiene targeting interventions in comparison to the conventional approaches 25,26–29 . Most of those interventional strategies were game based, such as using flashcards, connecting the dots, 28 completing crosswords and quizzes, 27 snake and ladder, self‐made story books 29 …”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation